Passive acoustic monitoring data recorded by recorder SV1028 at mooring AWI209-7 in the Weddell Sea, Southern Ocean, in 2013 - Karolin Thomisch; Stefanie Spiesecke; Katharina Lefering; Ramona Mattmüller; Sebastian Menze; Loretta Preis; Ilse Van Opzeeland; Sarah Zwicker; Olaf Boebel (PANGAEA, 2024)
Passive acoustic monitoring (PAM) data were collected by recorder SV1028 of type Sono.Vault (manufactured by develogic GmbH, Hamburg, Germany) at 66.6075° S, 27.121° W, mooring AWI209-7, in the Weddell Sea, Atlantic sector of the Southern Ocean. During a deployment period from January 2013 to January 2017, passive acoustic data were collected from January 2013 to October 2013 (recording period) by SV1028 as part of the Hybrid Antarctic Float Observing System (HAFOS) in the Weddell Sea. The recorder was moored at 1007 m depth and scheduled to record continuously at a sample rate of 5,333 Hz. Further details about the data acquisition and processing of this data set can be found in the accompanying metadata file (see Additional metadata) as well as the data processing report (see Data Processing Report). Passive acoustic data archived here represent data processing Level 2+ (see Data Processing Report), deviating from Standard Operation Procedure (SOP) Glossary (Thomisch et al. 2023a). Further information on data processing with regard to data preparation and standardization can be found in the associated SOP Part 1: Data preparation and standardization (Thomisch et al. 2023b).